Intravenous thrombolysis for acute ischemic stroke patients presenting with mild symptoms. Issue 5 (9th May 2012) - Strbian, Daniel; Piironen, Katja; Meretoja, Atte; Sairanen, Tiina; Putaala, Jukka; Tiainen, Marjaana; Artto, Ville; Rantanen, Kirsi; Häppölä, Olli; Kaste, Markku; Lindsberg, Perttu J.; ,
<x xml:space="preserve">Abstract</x> Background Thrombolysis of ischemic stroke patients presenting with mild symptoms is controversial. Aim We aimed to describe the clinical outcome and frequency of infarcts and symptomatic intracerebral hemorrhages on follow‐up imaging of such thrombolysis‐treated patients. Methods Our cohort included 1398 consecutive ischemic stroke patients treated with intravenous thrombolysis at the Helsinki University Central Hospital, years 1995–2010. We analyzed the patients according to baseline National Institutes of Health Stroke Scale: ≤2, 3–4, 5–6, and >6. In our institution, visualization of an artery occlusion or perfusion deficit is required for thrombolysis with National Institutes of Health Stroke Scale ≤ 2. We used univariate and multivariable methods to describe the cohort and study associations between the variables. Excellent three‐month outcome was defined as modified Rankin Scale 0–1. Results Fifty‐eight (4·1%) patients were treated with National Institutes of Health Stroke Scale ≤ 2, another 194 (13·6%) with 3–4 points, and 236 (16·5%) with 5–6 points. With National Institutes of Health Stroke Scale ≤ 2, 45 (78%) of the patients had excellent three‐month outcome, achieved in 116 (59%) patients with National Institutes of Health Stroke Scale 3–4, in 130 (55%) with National Institutes of Health Stroke Scale 5–6, and in 241 (26%) with National Institutes of Health Stroke Scale > 6. Frequencies of symptomatic intracerebral hemorrhage (European Cooperative Acute Stroke Study‐2) were 0%, 2·6%, 2·1%, and 8·1%, and visible infarcts on follow‐up imaging 48%, 43%, 48%, and 74%, respectively. In patients with baseline National Institutes of Health Stroke Scale ≤ 6, poor outcome was associated with previous stroke, diabetes, elevated admission blood glucose, and development of intracerebral hemorrhage. Conclusions Half of patients presenting with National Institutes of Health Stroke Scale 0–6 developed an infarction despite thrombolysis, and 40% had poor outcome, which was associated with glucose metabolism and hemorrhagic complications. Managing thrombolysis candidates with mild symptoms warrants individual consideration often supported by multimodal imaging.